School Principal Leadership Style in Islamic Boarding Schools-Based Junior High School - Agus Wiyoto; Bambang Budi Wiyono; Ery Tri Djatmika Rudijanto; Achmad Supriyanto (Kusuma Negara Business School, 2020)
This research aims to reveal the school principal leadership style in an Islamic boarding School-based junior high school located in Tulungagung Regency. This study is using a quantitative method with a phenomenological approach. The design used in this study is multicase studies with comparative case studies. The object of research includes Kiai, principals, vice-principals, teachers, and foundation employees, in three schools, there are (1) Sunan Gunung Jati Islamic Junior High school, (2) Jawaahirul Hikmah Junior High school, and (3) Al Azhaar Islamic Junior High School. Obtained research result related to the First Research Focus are as follows, (1) the path and goal of leadership style in Sunan Gunung Jati Islamic Junior High School, (2) the charismatic leadership style in Jawaahirul Hikmah Junior High School, (3) the situational leadership style in Al Azhaar Islamic Junior High School. Second, related to the roots of leadership in terms of religious roots, cultural roots, and social roots. First, the roots of leadership in terms of religious roots come from the letters in the Al-Qur'an and hadiths which explain the characteristics a leader must possess. Second, the root of leadership in terms of the cultural roots of sami'na wa atho'na means that the students always have high obedience to the kiai or ulama who are placed as heirs of the prophet. Third, the roots of leadership in terms of social roots show the fact that the background of the Islamic boarding school-based junior high school, the social background of the community, the highest decision-maker in the Islamic boarding school-based junior high school, the leadership model based on heredity, and the selection of principals based on competence, greatly influence the leadership style applied by each headmaster. This leadership root also influences the achievements of each of the Islamic boarding schools in Tulungagung. Keywords: Leadership Style, Leadership Root, Boarding Schools